The Influence of Store Atmosphere, Price and Product Quality on Purchasing Decisions at PT Modular Kuliner Indonesia Jakarta - Ananda, Rachelita Aurencia; Syahyuni, Dedy (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study examines the impact of store atmosphere, price, and product quality on consumer purchasing decisions on Hot Side Story products from PT Modular Kuliner Indonesia. By using a quantitative approach with multiple linear regression analysis, t-test, F test, and determination test using SPSS version 26 calculation tools and sig 0.05, it was found that the three variables produced a positive impact and reached significance for consumer purchasing decisions. Based on the results of the F test, the variables of price, product quality, and store atmosphere together (simultaneously) have a positive effect and have significance on consumer purchasing decisions. The findings of the determination test indicate that factors of product quality, pricing, and store atmosphere can all have an impact on 68.3% of variations in consumer purchasing decisions, and the remaining 31.7% are explained by external variables other than those carried out by researchers. This study provides three factors that drive consumer purchasing decisions on Hot Side Story products from PT Modular Kuliner Indonesia. So, the company still needs to continue to evaluate the store atmosphere, competitive prices, and improve product quality to encourage consumer purchasing decisions.